2006
DOI: 10.1111/j.1551-2916.2006.01299.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Densification of Zirconium Diboride Ceramics by Reactive Hot Pressing

Abstract: Zirconium diboride-silicon carbide ceramics with relative densities in excess of 95% were produced by reactive hot pressing (RHP) at temperatures as low as 16501C. The ZrB 2 matrix was formed by reacting elemental zirconium and boron. Attrition milling of the starting powders produced nanosized (o100 nm) Zr particulates that reacted with B below 6001C. The reaction resulted in the formation of nanoscale ZrB 2 crystallites that could be densified more than 2501C below the temperatures required for conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
113
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 37 publications
1
113
0
1
Order By: Relevance
“…A recent study on reactive hot pressing of Zr and B powders using differential thermal analysis 32 showed that the reaction between Zr and B occurs over a broad temperature range from 300 to 900°C, following a two-step process. It is likely that this process also consists of a combination of interdiffusion and crystallization processes, although diffusion in this case may be controlled by the presence of a native oxide on the Zr grains.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on reactive hot pressing of Zr and B powders using differential thermal analysis 32 showed that the reaction between Zr and B occurs over a broad temperature range from 300 to 900°C, following a two-step process. It is likely that this process also consists of a combination of interdiffusion and crystallization processes, although diffusion in this case may be controlled by the presence of a native oxide on the Zr grains.…”
Section: Discussionmentioning
confidence: 99%
“…[17] It has been recently shown that high energy milling of elemental Zr and B can be used to produce ZrB 2 at temperatures as low as 600°C, and dense ZrB 2 -SiC composites can be obtained at 1700°C. [18] Because boron compounds are cheaper and easier to handle, the present study is undertaken to systematically establish the possibility of lowering the process temperature by reactive densification of ZrB 2 -ZrC composites starting with Zr and B 4 C powders. In an earlier work on processing of TiN-TiB 2 composites, it was shown that a small amount of Ni (1 wt pct) addition to the starting Ti-BN mixture could substantially decrease the densification temperature from 1850°C to 1400°C.…”
Section: Introductionmentioning
confidence: 99%
“…Even though this process is cost-effective, it has been regarded as a lessthan-ideal technique to produce bulk ZrB 2 42 . The rapid heating rate (3,000 -4,000K/s 42,43 ) associated with the process results in incomplete reaction of Zr and B, and in the formation of non-equilibrium phases 42 . Similar observations were made in our previous work on reactive multilayer where impurities in Zr arising from the deposition process prevented complete reaction between B and Zr 21 .…”
Section: Tem Observationmentioning
confidence: 99%